The rebellious life of Mrs. Rosa Parks [large type] - Theoharis, Jeanne (Center Point Large Print, 2013)
The definitive political biography of Rosa Parks examines her six decades of activism, challenging perceptions of her as an accidental actor in the civil rights movement and presenting a corrective to the popular notion of Rosa Parks.